2010
DOI: 10.1016/j.neurobiolaging.2008.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Slowing of EEG correlates with CSF biomarkers and reduced cognitive speed in elderly with normal cognition over 4 years

Abstract: Our results suggest that already in cognitively healthy elderly subjects, biochemical changes in CSF, and the possible underlying neuropathologic processes it reflects, have an effect on cerebral function as visualized by the EEG rhythm and cognitive speed. It hereby suggests that CSF biomarkers and EEG theta activity might indicate early abnormal degenerative changes in the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 60 publications
7
69
0
Order By: Relevance
“…Prichep et al [18] demonstrated that baseline qEEG features such as increases in τ-power, slowing of mean frequency and changes in covariance among regions were differential predictors of cognitive decline in normal, subjectively impaired elderly subjects over 7 years of a follow-up interval. Stomrud et al [24] investigated by EEG and CSF analysis elderly individuals with repeated normal scores on cognitive tests over 4.5 years and found that increased T-tau protein and low Aβ42 in combination directly correlated with an increase in relative τ-power in qEEG as well as with slowing of cognitive speed. It is interesting that similarly to our findings it was an AD-associated profile of CSF biomarkers (increased T-tau and decreased Aβ42/P-tau ratio) that showed the strongest correlations with EEG and neuropsychological parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prichep et al [18] demonstrated that baseline qEEG features such as increases in τ-power, slowing of mean frequency and changes in covariance among regions were differential predictors of cognitive decline in normal, subjectively impaired elderly subjects over 7 years of a follow-up interval. Stomrud et al [24] investigated by EEG and CSF analysis elderly individuals with repeated normal scores on cognitive tests over 4.5 years and found that increased T-tau protein and low Aβ42 in combination directly correlated with an increase in relative τ-power in qEEG as well as with slowing of cognitive speed. It is interesting that similarly to our findings it was an AD-associated profile of CSF biomarkers (increased T-tau and decreased Aβ42/P-tau ratio) that showed the strongest correlations with EEG and neuropsychological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between T-tau protein and slowing of EEG global field power in AD was reported [23]. In healthy and cognitively normal elderly individuals, the combination of high T-tau protein and low Aβ42 proteins was correlated with an increase in the τ-power in the EEG [24]. Both studies used qEEG parameters and none of them applied the visual EEG assessment approach.…”
Section: Introductionmentioning
confidence: 99%
“…In cognitively normal elderly subjects, CSF total-tau and p-tau levels as well as the combined p-tau/Aβ42 ratio are associated with relative EEG theta power, especially in posterior brain regions. This increase in theta power correlates with a slowing of cognitive speed, indicating that increased theta oscillations in posterior regions may represent an early sign of neurodegeneration in the brain [33]. This activity is often interpreted as a slowing of alpha rhythm, In line with this view, the results of the study by Finnigan and Robertson [34], on healthy elderly subjects, proposed the existence of 2 forms of theta frequency oscillation, one indicative of healthy neurocognitive function and the other representing an EEG/alpha slowing linked to future substantial cognitive decline .…”
Section: Aging and Cortical Oscillationsmentioning
confidence: 99%
“…The second approach is represented by use of psychometric tasks (cognitive testing) like the d2-test for concentration, a memory test or performance of arithmetic calculations [8]. The third approach very often is covered by a neurophysiological methodology, usually recording of quantitative electroencephalography [9] [10] or biochemical parameters from cerebrospinal fluid [11]. Thus, a combination of measurements on these three levels should be able to provide a quantitative definition of mild cognitive impairment and fulfil the criteria for an early diagnosis and recognition of the risk potential.…”
Section: Introductionmentioning
confidence: 99%